Penerapan Teknik Vokal Artikulasi pada Lagu Indahnya Saat Teduh oleh Pemimpin Pujian di Gereja Methodist Indonesia Sukarame Baru Resort Sukasari Labuhan Batu Utara Tahun Pembelajaran 2023/2024 - Helmalia Diwani Lumban Tobing; Eben Haezarni Telaumbanua; Monang Asi Sianturi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This research aims to find out good vocal training techniques for singing for worship leaders by applying articulatory vocal techniques. Articulated vocal technique is the pronunciation of the words in the song lyrics clearly and correctly so that the message and meaning of the song being sung can be heard clearly to the listener. The method used in this research stage is descriptive qualitative method. The stages of research on the application of vocal articulation techniques carried out include observation, interviews and documentation. The objects of this research were five worship leaders at GMI Sukarame Baru Resort Sukasari Labuhan Batu Utara. In the implementation process, researchers held six meetings providing material and singing practice according to correct vocal technique. In this research process, the worship leader practiced articulation repeatedly singing the song